2019
DOI: 10.1063/1.5066080
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of resolution in microspherical nanoscopy by coupling of fluorescent objects to plasmonic metasurfaces

Abstract: The resolution of microsphere-based nanoscopy is studied using fluorescently labeled nanospheres and F-actin protein filaments with the emission coupled to the localized surface plasmon resonances in the underlying Au nanodisk arrays. Virtual imaging is performed through high-index microspheres embedded in plastic coverslips placed in contact with the nanoscale objects. For 150 and 200 nm periods of nanoplasmonic arrays, the imaging has a solid immersion lens-limited resolution, whereas for shorter periods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…For optoplasmonic hybrid structures composed of BTG microspheres and BD substrates, the focused light from the microspheres effectively guides the incident light on plasmonic components (BD substrates). Through plasmonic–photonic interactions, the electric field at the gaps among nanoparticles and the contacting area between nanoparticles and BD substrates is enhanced. Thus, the optoplasmonic structure serves as an intense near-field excitation source for the nanoparticles nearby. It has been demonstrated that the dielectric nanoparticles can be re-excited by the increased evanescent waves and it causes a new round of scattering to the far field, which provides more information in the far field .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For optoplasmonic hybrid structures composed of BTG microspheres and BD substrates, the focused light from the microspheres effectively guides the incident light on plasmonic components (BD substrates). Through plasmonic–photonic interactions, the electric field at the gaps among nanoparticles and the contacting area between nanoparticles and BD substrates is enhanced. Thus, the optoplasmonic structure serves as an intense near-field excitation source for the nanoparticles nearby. It has been demonstrated that the dielectric nanoparticles can be re-excited by the increased evanescent waves and it causes a new round of scattering to the far field, which provides more information in the far field .…”
Section: Resultsmentioning
confidence: 99%
“…23,25 By using optoplasmonic structures, Zhang and Lei observed fluorescent nanoparticles with a size of 100 nm, 24 and Brettin et al demonstrated that the resolution in imaging fluorescent objects could reach to ∼ λ/7. 25 For a fluorescent object, the absolute signals obtained in scattering and fluorescence modes under identical illumination and imaging conditions are quite different, and the scattering intensity is weaker than the fluorescence intensity for a small object. 26 While imaging nonfluorescent objects, only scattering mode signals are obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include a possibility of excitation of LPs in nanostructured metals as well as SPPs in semiconductor and dielectric structures. [ 88,160–162 ] It was also shown that substrates play an important role in imaging magnification and resolution. Theoretical research shows the imaging resolution and the magnification factor are both relative to the refractive index of the substrate.…”
Section: Superresolution Imaging Based On Sfc Methodsmentioning
confidence: 99%
“…However, achieving of λ/6 − λ/8 resolution requires additional objects been involved, for example, plasmonic particles, wires and gratings [9][10][11]. Instead, labeling of small objects with fluorescent molecules can also greatly enhance resolution [12,13]. Some authors even claim resolution of minimal features down to λ/17.…”
Section: Introductionmentioning
confidence: 99%